Antibacterial activity of betel (Piper betle L.) fruit against Pseudomonas aeruginosa - Annisa Hamka; Fatimawali Fatimawali; Olvie Syenni Datu; Trina Ekawati Tallei (Indonesian Society for Biochemistry and Molecular Biology, 2021)
Background: Betel (Piper betle L.) is a well-known medicinal plant for its numerous health benefits. Saponins, flavonoids, polyphenols, and essential oils are among the chemical constituents of betel plants. Flavonoids are one of the most common groups of secondary metabolites found in plant tissues, including in betel plants. Objective: The purpose of this research is to isolate flavonoids from betel fruit and to determine the antibacterial activity of betel fruit extract against Pseudomonas aeruginosa. Methods: Thin-layer chromatography (TLC) with the eluent chloroform: methanol: water was used to isolate flavonoids. UV-Vis spectrophotometry was used to determine the presence of flavonoids in betel fruit. The antibacterial activity of extract and TLC-isolates of betel fruit was tested by using the disc method. Results: TLC analysis resulted in the formation of a brown stain. The UV-Vis spectrophotometry results revealed two absorption bands at 366 nm and 268 nm, indicating that flavonoids are present in betel fruit. Antibacterial activity test against Pseudomonas aeruginosa bacteria showed that the concentration of 30% and 60% of betel fruit extract had strong antibacterial activity. Conclusion: The results revealed that the betel fruit contains flavonoid compounds, and the extract has medium to strong antibacterial activity.